DIFFERENTIAL INTROGRESSION IN A MOSAIC HYBRID ZONE REVEALS CANDIDATE BARRIER GENES. (23rd July 2013) - Larson, Erica L.; Andrés, Jose A.; Bogdanowicz, Steven M.; Harrison, Richard G.
<x xml:space="preserve">Abstract</x> Hybrid zones act as genomic sieves. Although globally advantageous alleles will spread throughout the zone and neutral alleles can be freely exchanged between species, introgression will be restricted for genes that contribute to reproductive barriers or local adaptation. Seminal fluid proteins (SFPs) are known to contribute to reproductive barriers in insects and have been proposed as candidate barrier genes in the hybridizing field crickets Gryllus pennsylvanicus and Gryllus firmus. Here, we have used 125 single nucleotide polymorphisms to characterize patterns of differential introgression and to identify genes that may contribute to prezygotic barriers between these species. Using a transcriptome scan of the male cricket accessory gland (the site of SFP synthesis), we identified genes with major allele frequency differences between the species. We then compared patterns of introgression for genes encoding SFPs with patterns for genes expressed in the same tissue that do not encode SFPs. We find no evidence that SFPs have reduced gene exchange across the cricket hybrid zone. However, a number of genes exhibit dramatically reduced introgression, and many of these genes encode proteins with functional roles consistent with known barriers.